Efficient Identification of Causal Mutations through Sequencing of Bulked F2 from Two Allelic Bloomless Mutants of Sorghum bicolor - Jiao, Yinping; Burow, Gloria; Gladman, Nicholas; Acosta-Martinez, Veronica; Chen, Junping; Burke, John; Ware, Doreen; Xin, Zhanguo (Frontiers in Plant Science, 2018)
Sorghum (Sorghum bicolor Moench, L.) plant accumulates copious layers of epi-cuticular wax (EW) on its aerial surfaces, to a greater extent than most other crops. EW provides a vapor barrier that reduces water loss, and is therefore considered to be a major determinant of sorghum’s drought tolerance. However, little is known about the genes responsible for wax accumulation in sorghum. We isolated two recessive allelic mutants, bloomless40-1 (bm40-1) and bm40-2, from a mutant library constructed from ethyl methane sulfonate (EMS) treated seeds of the inbred sorghum line BTx623. Both mutants were nearly devoid of the EW layer. Each bm mutant was crossed to the un-mutated BTx623 to generated F2 populations that segregated for the bm phenotype. Genomic DNA from 20 bm F2 plants from each population was bulked for whole genome sequencing. A single gene, Sobic.001G228100, encoding a GDSL-like lipase/acylhydrolase, had unique homozygous mutations in each bulked F2 population. Mutant bm40-1 harbored a missense mutation in the gene, whereas bm40-2 had a splice donor site mutation. Our findings thus provide strong evidence that mutation in this GDSL-like lipase gene causes the bm phenotype, and further demonstrate that this approach of sequencing two independent allelic mutant populations is an efficient method for identifying causal mutations. Combined with allelic mutants, MutMap provides powerful method to identify all causal genes for the large collection of bm mutants in sorghum, which will provide insight into how sorghum plants accumulate such abundant EW on their aerial surface. This knowledge may facilitate engineering drought-tolerance in other crops.